Transformation of Digital Marketing the Coffee Production in COVID-19 Pandemic : Islamic Economic Paradigm - Kurniawan, Muhammad; Normasyhuri, Khavid; Pujianti, Eva (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: This study aims to determine transformation of development through digital marketing in maintaining coffee production in West Lampung in the midst of the COVID-19 pandemic in the Islamic economic paradigm.Design/Method/Approach: The research uses qualitative methods with an approach post positivism philosophy. Secondary data was obtained from BPS and primary data was obtained from interviews with West Lampung Coffee SMEs. The data collection method uses several stages: Observation, Interview and Documentation. Data Processing and Validity includes: Credibility, Dependability, Transferability and Confirmability.Findings: The digital marketing transformation of coffee production SMEs coffee in West Lampung during the COVID-19 pandemic has brought about significant changes in the way business is done. SMEs coffee companies that are able to implement digital marketing strategies effectively can expand market reach, increase sales, and improve their overall business performance.Organally/Value: This research can provide new insights on how coffee SMEs in West Lampung can use digital marketing to increase coffee production and marketing effectively during the COVID-19 pandemic. In addition, this research can also provide insight into the latest trends and innovations in the use of digital marketing in the coffee industry.Â